Meningkatkan Kesadaran Masyarakat Desa Ujung Pandaran Terhadap Dampak Membuang Sampah di Laut - Nurul Aima; Nurul Shabah; Putri Alisa Firlana; Nurul Huda; Putri Putri; Bagus Andy Winarno; Bima Saputra (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The community service carried out by university students during the community service program (KKN) explained the dangers of dumping waste into the sea in Ujung Pandaran Village, as many coastal residents of Ujung Pandaran Village still dispose of their household waste into the ocean. This service aims to raise awareness among the people of Ujung Pandaran Village to stop dumping waste into the sea and instead dispose of it by sorting the waste according to its type. The method used in this article is a qualitative approach through observation, interviews, and documentation. The conclusion of this article is that through waste management outreach at SMP Negeri Satu Atap 1 Teluk and the distribution of brochures to the residents of Ujung Pandaran Village, it is hoped that the community will become more aware of the need to avoid dumping waste into the sea. Additionally, in the future, it is expected that more waste disposal sites (TPS) will be available in every neighborhood (RT) in Ujung Pandaran Village, making waste management easier and more effective.